2015
DOI: 10.1111/aphw.12044
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Alcohol Pre-Drinking in Australian Undergraduate Students Using an Integrated Theoretical Model

Abstract: Results provide support for the hypothesised model relationships. Autonomous motivation, attitude, subjective norm, and perceived behavioural control were influential in forming students' intentions to pre-drink. However, consistent with previous findings, the intention-behaviour relationship was relatively weak. Future research should look to non-intentional and volitional processes that may influence pre-drinking in undergraduates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 73 publications
(132 reference statements)
3
26
0
Order By: Relevance
“…These factors are consistent with research that has identified cost and availability of alcohol as key determinants of excessive alcohol consumption, particularly in young people [43][44][45][46][47]. This is particularly important for policy makers as it seems that participants considered the increasing affordability of alcohol to be the most significant contributor to its growing availability, not extended opening hours.…”
Section: Discussionsupporting
confidence: 83%
“…These factors are consistent with research that has identified cost and availability of alcohol as key determinants of excessive alcohol consumption, particularly in young people [43][44][45][46][47]. This is particularly important for policy makers as it seems that participants considered the increasing affordability of alcohol to be the most significant contributor to its growing availability, not extended opening hours.…”
Section: Discussionsupporting
confidence: 83%
“…Participants completed multi-item self-report measures of study constructs based on published guidelines and measures used in previous studies (Caudwell & Hagger, 2015;Hagger, Chatzisarantis, & Harris, 2006;Job et al, 2010;Patton, Stanford, & Barratt, 1995;Tangney et al, 2004) and the self-control IAT developed specifically for the current study. Complete study measures including items, response scales, and sources are provided in Appendix S1.…”
Section: Methodsmentioning
confidence: 99%
“…Although less is known about the relationship between pregaming attitudes and behavior, Caudwell and Hagger (2015) found a positive bivariate correlation as well as a significant pathway from more positive attitudes about pregaming to greater pregaming participation that was mediated by intentions to pregame. According to the theory of reasoned action, attitudes and perceived peer norms independently explain behavior (Ajzen, 1988).…”
Section: Introductionmentioning
confidence: 76%
“…To our knowledge, only two studies have examined the effects of injunctive norms on pregaming. In Caudwell and Hagger's (2015) study, greater perceived approval from others about one's engagement in pregaming was correlated with pregaming frequency and predicted pregaming via greater intentions to pregame (Caudwell & Hagger, 2015). In Rutledge, McCarthy, and Lendyak (2014), pregame-specific injunctive norms was a significant predictor of alcohol consumed while pregaming (i.e., pregaming quantity) among men, independent of pregaming descriptive norms.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation